Painel de gestão acadêmica dos cursos de graduação do Instituto Federal de Educação, Ciência e Tecnologia de Sergipe: uma proposta de Power BI como ferramenta gerencial - Parisi, Baby de Fátima Barbosa (2020)
In a dynamic scenario, where public institutions seek excellence in their management and consequently improvements of public services, knowledge management is one of the best practices adopted. The implementation of the concept assists in the evaluation and monitoring of specific strategic categories, as well as the exercise of active transparency. This is an urgent demand from society, arising from the need to monitor the application of public resources and knowledge about decisions according to managers. Therefore, the use of a decision support tool does not only benefit the managers who are at the head of the agencies, but also provides the use of information technology instruments, especially Business Intelligence, as a way to ensure agility and processing information. This research offers the construction of an academic management panel, using Power BI as a tool to facilitate data control, monitoring and analysis at the Federal Institute of Education, Science and Technology of Sergipe (IFS). This proposal intends to facilitate the decision-making process of managers, in addition to allowing efficiency in active transparency and also mitigating the bottlenecks in accessing and managing the data already available. The methodology used allows the practical application of the object of study, demonstrating that this approach can be multiplied by other public institutions of higher education. The results obtained confirmed that the technical product, the result of this investigation, is capable of presenting, in a dynamic and agile way, an overview of the main strategic dimensions of teaching. The academic management panel provides information covering the selection process, student profile, details on graduates, dropout and teachers. In addition to these, were also exposed, through a historical series, the main indicators established by Judgement 2,267/2005/TCU and Ordinance 429/2020/MEC/INEP, which guides public actions developed by IFS, controlled by the Federal Government and accompanied by the main control bodies.